Noncoding RNAs in Drug Resistance of Gastrointestinal Stromal Tumor - Li, Jiehan; Guo, Shuning; Sun, Zhenqiang; Fu, Yang (Frontiers in Cell and Developmental Biology, 2022)
Gastrointestinal stromal tumor (GIST) is the most common mesenchymal tumor in the gastrointestinal tract and a model for the targeted therapy of solid tumors because of the oncogenic driver mutations in KIT and PDGDRA genes, which could be effectively inhibited by the very first targeted agent, imatinib mesylate. Most of the GIST patients could benefit a lot from the targeted treatment of this receptor tyrosine kinase inhibitor. However, more than 50% of the patients developed resistance within two years after imatinib administration, limiting the long-term effect of imatinib. Noncoding RNAs (ncRNAs), the non-protein coding transcripts of human, were demonstrated to play pivotal roles in the resistance of various chemotherapy drugs. In this review, we summarized the mechanisms of how ncRNAs functioning on the drug resistance in GIST. During the drug resistance of GIST, there were five regulating mechanisms where the functions of ncRNAs concentrated on: oxidative phosphorylation, autophagy, apoptosis, drug target changes, and some signaling pathways. Also, these effects of ncRNAs in drug resistance were divided into two aspects. How ncRNAs regulate drug resistance in GIST were further summarized according to ncRNA types, different drugs and categories of resistance. Moreover, clinical applications of these ncRNAs in GIST chemotherapies concentrated on the prognostic biomarkers and novel therapeutic targets. Contribution to the field: This review discussed the potential mechanisms of ncRNAs in the drug resistance of GIST, which provides novel insights into exploring the therapeutic roles of ncRNAs as intervened targets and prognostic biomarkers for GIST with drug resistance.